Pola Relasi Antara Peserta Didik dan Pendidik dalam Perspektif Filsafat Pendidikan Islam Kontemporer - Sania, Fitri (Universitas Indraprasta PGRI Jakarta, 2025)
In developing a complete personality, the dynamics between teacher and student are very important. This paper seeks to explore the significance of the relationship between teacher and student within the framework of modern Islamic pedagogical theory. Books, online papers, and previous research are the main sources from the library collection, which is the research methodology used here. Investigating the ideas put forward by prominent figures such as Seyyed Hossein Nasr, Fazlur Rahman, Syed Muhammad Naquib al-Attas, Ismail Raji al-Faruqi, and Taha Jabir al-Alwani requires a thorough examination of the collected data. From this, relevant conclusions can be drawn to develop concepts such as adab, critical dialog, holistic education, knowledge integration, and ijtihad. The findings of this study show that, according to modern Islamic educational philosophy, the best model of teacher-student interaction is one characterized by open communication, mutual respect, and an emphasis on developing students' spirituality, critical thinking skills, and character. We can deal with the problems of modern education, such as the crisis of values, the crisis of the meaning of life, the crisis of the credibility gap, and the crisis of idealism, by looking at the pattern of the relationship between learners and educators through the lens of contemporary Islam. In order to prepare learners to cope with the complex problems of the future, it is necessary to incorporate the ideas of Islamic education into the modern education system.